Skeleton of a dwarf from excavations - Farkas, Gyula; Nagy, Endre; Kósa, Ferenc (Acta Biologica Szegediensis, 2001)
The authors describe the skeleton remains of a dwarf with achondroplasia dating from the 13th century. The finding is from a Hungarian site and can be found in the historical anthropological collection at the Department of Anthropology of the University of Szeged.